Problematika Kesehatan Mental di Era Disrupsi dan Solusinya dalam Al-Qur’an- Hadis - Nursaimaputri; Tulus Musthofa; Nur Saidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Fundamental changes take the form of technological evolution that looks for loopholes to influence human life. The current era of revolutionary transformation has triggered widespread mental health disorders in Indonesia which continue to increase. It is noted that the majority of suicide cases in Indonesia are young people and the biggest factor is mental health. Because mental health greatly influences a person's quality of life. Currently we have entered the disruption phenomenon, which is a major part of the global scale. Where in the era of disruption there is a mental health crisis. It can be seen that cases of young people are increasing. The aim of this research is to find out mental health in the era of disruption and the solutions in the Al-Qur-an and Hadith. The method used in this research is library research, namely a series of activities relating to library data collection methods. This research uses a qualitative approach and then describes it descriptively. For the results, the solution is to build one's foundation with the Al-Qur'an, multiply good works and avoid evil (amar ma'ruf nahi munkar). Build a good relationship with Allah by remembering Him more (dhikr). Then develop relationships with others and their environment. The source of a human's strength lies in his self-esteem. Self-esteem is the most important axis in strengthening mental health.